Revising the Original Antonovsky Sense of Coherence Concepts: A Mixed Method Development of the Sense of Meaning Inventory (SOMI) - Denise M. Saint Arnault; Zeynep Zonp (Sexes)
Trauma recovery research requires the development of instruments that capture gender-based violence (GBV) survivor recovery phases. The salutogenic concepts in Antonovsky’s Sense of Coherence (SOC) (manageability, comprehensibility, and meaning) could help capture trauma recovery stages, but the factorial structure of the SOC-13 has remained problematic. Moreover, most SOC revisions generally abandon the original intent of the SOC-13, developing scales that capture essential but different aspects of positive psychology. This study used mixed methods to develop the Sense of Meaning Inventory (SOMI), preserving the original concepts but updating the language, removing cultural idioms, and revising the response scales to stabilize the subscales. The qualitative phase evaluated and updated the items of the scale while retaining the original concepts. The quantitative phase conducted a two-sample psychometrics reliability and validity evaluation of the new scale with GBV survivors, finding a three-factor solution. This scale may be more amenable for international research and theory testing in GBV and other health conditions.